Enhancing active radial distribution networks by optimal sizing and placement of DGs using modified crow search algorithm - Mohamed Abdelbadea; Tarek A. Boghdady; Doaa Khalil Ibrahim (Institute of Advanced Engineering and Science, 2019)
Incorporating many Distributed Generators (DGs) technologies in power system networks has grown rapidly in recent years. Distributed generation (DG) plays a key role in reducing power loss and enhancing the voltage profile in radial distribution networks. However, inappropriate DGs site or size may cut network efficiency; moreover, injecting harmonics is one of the integration concerns of inverter-based DGs. Two-procedure based approach is introduced in this paper. The first procedure solves the DGs siting and sizing problem, as a multi-objective one by improving the voltage profile of the whole distribution network and also reducing its power loss. A weighted sum method is presented to create the Pareto optimal front in this procedure and get the compromised solution by applying a novel metaheuristic optimizer, named Crow Search Algorithm (CSA). A modification on CSA is also proposed and applied to improve its performance. The achieved solution for inverter-based DGs placement and size is checked in the second procedure to make sure the accepted voltage THD at all buses by implementing detailed simulation for the tested system using Matlab/Simulink. The proposed approach has been tested on IEEE 33-bus radial distribution system with photovoltaic DGs. To confirm the superiority of the modified CSA algorithm in terms of quality of solution, its achieved results are compared with the results offered by the original CSA algorithm and published results of some other nature-inspired algorithms.